2019
DOI: 10.3390/jpm9040047
|View full text |Cite
|
Sign up to set email alerts
|

Physician Experience with Direct-To-Consumer Genetic Testing in Kaiser Permanente

Abstract: Health systems and physicians nationwide aspire to consistently and reliably apply genetic and genomic information to guide disease prevention, management, and treatment. However, clinical information, including genetics/genomics data from within and outside of the care delivery system, is expanding rapidly. Between November 2017 and April 2018, we surveyed 1502 Permanente Medical Group primary care and specialist physicians to assess the degree to which direct-to-consumer genetic test results were being prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…The e-mail notice was successfully delivered to 358 HCPs (42 returned e-mails due to a full inbox or inactive e-mail address), of which 72 provided informed consent for the study for a response rate of 20%. This response rate is higher than previous studies that have investigated HCP experiences with DTC GT in practice, which have reported response rates between 2 and 15% [14-16]. The survey was open for a period of 8 weeks, with 3 reminder e-mails sent on a biweekly interval following the initial invitation.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…The e-mail notice was successfully delivered to 358 HCPs (42 returned e-mails due to a full inbox or inactive e-mail address), of which 72 provided informed consent for the study for a response rate of 20%. This response rate is higher than previous studies that have investigated HCP experiences with DTC GT in practice, which have reported response rates between 2 and 15% [14-16]. The survey was open for a period of 8 weeks, with 3 reminder e-mails sent on a biweekly interval following the initial invitation.…”
Section: Methodsmentioning
confidence: 98%
“…Consequently, the knowledge and competence of HCPs with NGT are a growing priority [11-13]. While the experiences of HCPs with DTC genetic tests have been studied [14-16], research on the HCP clinical experience with NGT is at its infancy. Previous reports regarding NGT perceptions have reported a prominent knowledge gap among HCPs and students in training about how to incorporate NGT in practice and also a frequently reported desire for additional sources of nutrigenomics education [17-22].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies show that the majority of non-genetics providers report low confidence in genetic concepts, testing and interpretation of results [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. High levels of confidence as to when to refer to a genetic specialist have been reported [ 12 ], though this was lower in primary care providers (PCPs) than specialty providers. Specifically, non-genetics providers cite challenges related to genomic terminology and the volume of information in genetic laboratory reports [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that more than 26 million people in total have ordered some flavor of DTC testing [1,2]. A recent survey of primary care and specialist physicians found that 35% of respondents report having received a DTC genetic result from a patient [3]. It is also becoming increasingly common for consumers to submit their raw array data to third party websites for interpretation, such as Promethease, codegene.eu, or WeGene [4,5].…”
mentioning
confidence: 99%